E-procurement: Evolution and adoption. A review of Literature - Watuleke, Joseph (IJRDO- Journal of Educational Research, 2017)
This paper presents an exploratory literature on the concept of e-procurement. The aim was to understand the concept of e-procurement, its evolution and adoption in the market economy as well as higher education. It was established that whereas e-procurement has had a rapid growth in the manufacturing sector, a lot is still desired in the higher education sector following the slow pace of adoption.